Pengaruh Kecukupan Modal, Risiko Kredit, Risiko Likuiditas dan Pengelolaan Aset Produktif Terhadap Profitabilitas : Studi Keuangan pada Bank Umum Swasta Nasional yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Ulpa, Fhirda Putriana; Jhoansyah, Dicky; Sunarya, Erry (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A bank's profitability is an important indicator of its financial health and future aspirations. Increasing profitability requires effective, efficient management and building public trust. The aim of this research is to determine the effect of Capital Adequacy Ratio, Non Performing Loans, Loan to Deposit Ratio, and Net Interest Margin on Returns on Assets for the period 2019 to 2022. The population in this research is financial reports on the Indonesia Stock Exchange (BEI). The objects of this research are Capital Adequacy Ratio (X1), Non Performing Loans (X2), Loan to Deposit Ratio (X3), Net Interest Margin (X4) and Return On Assets (Y). The research method used is descriptive and associative with a quantitative approach. The data analysis techniques used in this research are statistical and descriptive. Which uses a number of tests such as the classic assumption test which consists of normality test, multicollinearity, heteroscedasticity, multiple linear regression analysis, multiple correlation coefficient, coefficient of determination, hypothesis test (t test) and (f) test using the SPSS application. The research results show that from the t test (partial) the Capital Adequacy Ratio partially shows a result of 0.019 where tcount is 0.019<ttable 2.021 with a significance value of 0.019, next for Non Performing Loans shows Tcount<Ttable (0.145<2.021) with a significance value of 0.145, then for Loan to Deposit Ratio shows a Tcount of 0.035<Ttable 2.021 with a significance value of 0.035 and Net Interest Margin shows a Tcount of 0.001<Ttable 2.021 with a significance value of 0.001. The conclusion is that CAR, NPL, LDR partially have no influence on Return On Assets, while NIM partially has an influence on profitability.